THE EFFECT OF SYNECTICS TECHNIQUE ON GRADE TEN STUDENT’S VOCABULARY ACQUISITION - Firdha Uzhami; Nurul Hasanah Fajaria (Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2018)
The research consists of two variables, namely the independent variable (Synectics Technique)and the dependent variable (Vocabulary Acquisition). The purpose of this research is to findout whether or not there is significant effect of synectics technique on students’ vocabularyacquisition. This research was conducted on grade ten students of SMK Budi Perkasa TambunSelatan in academic year of 2017/2018. Research method used in this research was quasiexperimental, quantitative and the design was randomized post-test only control group design.The analysis using SPSS-based One Way Anova Formula produced significance (Sig.) valueof 0.033. since the significance value was smaller than (<)0.05, Ho is rejected and HAisaccepted. (Fobserved)5.018 also showed that is higher than the critical value of (Ftable) (at thesignificant level of 0.05 and df (1; 60)), namely 4.02. it can be concluded that Fobserved (5.018)> Ftable (4.02). Accordingly the research concludes that there is significant effect of synecticstechnique on grade ten students’ vocabulary acquisition at SMK Budi Perkasa Tambun Selatanin the Academic Year of 2017-2018.